2000
DOI: 10.1155/2000/825727
|View full text |Cite
|
Sign up to set email alerts
|

Dysexecutive Syndrome in Schizophrenia: A Cross‐Cultural Comparison between Japanese and British Patients

Abstract: This study tested the hypothesis that the dysexecutive syndrome of schizophrenia is impervious to cultural differences. 18 Japanese and 22 British patients and 14 Japanese and 19 British control subjects were compared on the BADS (Behavioural Assessment of Dysexecutive Syndrome), a comprehensive neuropsychological assessment battery, designed for 'ecological validity', and other measures of frontal executive functions (EFs). Both cultural groups of schizophrenic patients showed equally severe impairment in mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
2
5
0
1
Order By: Relevance
“…While the use of the BADS‐C has not yet been reported in the literature, the adult version of the test has been utilized with a range of patient populations. The BADS therefore appears to be sensitive at detecting executive dysfunction in schizophrenic patients [Cools, Brouwer, de Jong, & Slooff, 2000; Evans, Chua, McKenna, & Wilson, 1997; Ihara, Berrios, & McKenna, 2000, 2003; Katz, Tadmor, Felzen, & Hartman‐Maeir, 2007; Krabbendam, de Vugt, Derix, & Jolles, 1999], drug users [Verdejo‐Garcia & Perez‐Garcia, 2007; Zakzanis & Young, 2001], chronic alcoholics [Moriyama et al, 2002], patients with depression [Paelecke‐Habermann, Pohl, & Leplow, 2005], patients with Parkinson's disease [Kamei et al, 2008] patients with Alzheimer's disease [Amanzio, Geminiani, Leotta, & Cappa, 2008] and patients with traumatic brain injury [Bach, Happé, Fleminger, & David, 2006; Bennett, Ong, & Ponsford, 2005a,b]. Most of the subtests also appear to have good test‐retest reliability [Jelicic, Henquet, Derix, & Jolles, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…While the use of the BADS‐C has not yet been reported in the literature, the adult version of the test has been utilized with a range of patient populations. The BADS therefore appears to be sensitive at detecting executive dysfunction in schizophrenic patients [Cools, Brouwer, de Jong, & Slooff, 2000; Evans, Chua, McKenna, & Wilson, 1997; Ihara, Berrios, & McKenna, 2000, 2003; Katz, Tadmor, Felzen, & Hartman‐Maeir, 2007; Krabbendam, de Vugt, Derix, & Jolles, 1999], drug users [Verdejo‐Garcia & Perez‐Garcia, 2007; Zakzanis & Young, 2001], chronic alcoholics [Moriyama et al, 2002], patients with depression [Paelecke‐Habermann, Pohl, & Leplow, 2005], patients with Parkinson's disease [Kamei et al, 2008] patients with Alzheimer's disease [Amanzio, Geminiani, Leotta, & Cappa, 2008] and patients with traumatic brain injury [Bach, Happé, Fleminger, & David, 2006; Bennett, Ong, & Ponsford, 2005a,b]. Most of the subtests also appear to have good test‐retest reliability [Jelicic, Henquet, Derix, & Jolles, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…We [18] have already reported that both Japanese and British groups of schizophrenic patients showed equally severe impairment on most executive tests including the BADS. In that study 18 Japanese and 22 British patients and 14 Japanese and 19 British control subjects were compared on the BADS and other measures of frontal executive functioning.…”
Section: Discussionmentioning
confidence: 84%
“…Bobes et al [5] also found comparable abnormalities of event-related potential N400 in Cuban and Chinese patients. We [18] have already reported that, in spite of major cultural differences, Japanese and British schizophrenic patients do not differ much in terms of their neuropsychological dysexecutive profiles. These studies, however, remain incomplete in that they can only demonstrate resemblance at a single level: symptomatic, neurophysiological or neuropsychological.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The total profile score and profile scores of each subtest in this Japanese version were confirmed to have an identical potential against the original version of the BADS 23. Moreover, Ihara et al reported that the Japanese version was consistent with the original version of the BADS based on comparative data for Japanese and English ExD patients 24. It is therefore possible to classify the standardized score on the BADS into five grades: impaired, borderline, low average, average, high average, and superior, in the same manner as in the traditional IQ test.…”
mentioning
confidence: 95%